The Effect of Mindful Breathing and Mindful Sitting Practices on Nanyang Zhi Hui High School Students in Medan - Ferry, Ferry; Kabri, Kabri; Surya, Julia (Green Publisher Indonesia, 2023)
The research objective was to determine the effect of mindful breathing and mindful sitting practices on the academic stress of Nanyang Zhi Hui High School students in Medan. The population in this study was 82 high school students who had known and participated in the practice of mindful breathing and mindful sitting for 5 years. Data collection methods are questionnaires and documentation as support. Methods of data analysis using inferential statistics with a quantitative approach and multiple linear regression. The data that has been collected is tested for validity and reliability, which is then analyzed using inferential statistical methods. The results showed that the practice of mindful breathing had an effect on the academic stress of Nanyang Zhi Hui Medan High School students by 6.6%, the practice of mindful sitting had an effect on the academic stress of Nanyang Zhi Hui Medan High School students by 5.8% and the practice of mindful breathing and mindful sitting together (simultaneously) had an effect on the academic stress of Nanyang Zhi Hui High School students by 13.6%, with the variable of mindful breathing practice providing an effective contribution of 7.17% while the variable of mindful sitting practice providing an effective contribution of 6.41%. Based on the results of the study, it can be concluded that the practice of mindful breathing and mindful sitting has a significant effect on the academic stress of Nanyang Zhi Hui High School students.